Agricultural biomass feedstock for biofuels production in Ukraine - Tryboi, Oleksandra; Zheliezna, Tetiana; Drahniev, Semen (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Ukraine has a large potential of biomass available for the production of solid, gaseous and liquid biofuels. According to 2021 data, the bioenergy potential is about 25 Mtoe, of which 49% is agricultural residues and 30% is energy crops (in case of growing on 2 mln ha). Of the agriresidues, only sunflower husk is now widely used for energy, while the potential of straw, corn stalks and sunflower stalks is practically untapped for this purpose. For Ukraine, one of the promising directions is priority use of corn stalks for the production of energy and solid biofuels such as briquettes and pellets. Another prospective area is growing energy crops. Ukraine has 3-4 mln ha of unused (marginal) agricultural land, which can be engaged for growing energy crops such as willow, poplar, miscanthus (for solid biofuels) and corn silage for biogas. Growing energy crops as biomass feedstock and its further use for the production of heat and power becomes competitive in light of growing prices of natural gas and issues with providing security of its supply. An important but less-developed sector of Ukraine’s bioenergy is motor biofuels. Having such a big potential of agribiomass, the country could produce bioethanol and biodiesel including the advanced biofuels from lignocellulosic feedstock. It is necessary to create favourable conditions for the development of domestic production of motor biofuels. This may include a reduction in the excise tax, the abolition of compulsory tax bill for the full rate of excise duty when transporting bioethanol, the introduction of an export duty on rapeseed, and some other measures.